Promotion Influence in Sales Advance and in Increasing the Image to the SMEs in Kosova - Arapi, Rajan (European Journal of Sustainable Development, 2013)
The promotion as an important element of marketing mix plays a key role in marketingmanagement regard, in every enterprise, and also for SMEs. The SMEs in Kosova aregiving more and more importance to the promotion, and this factor, beside the salesadvance for their products, is important to increase their image. What is the impact of thepromotion in SMEs longevity; respectively ëhat are the advantages and disadvantages ofpromotion application compared with the other traditional advertisement forms? Whatare the promotion models used by the advance companies to increase their sales level andimprove the service level ? These are some of the research questions that follow thispaper. On the other side the increasing promotion application in front of traditionalforms of Marketing have made SMEs to save from their budget dedicated to Marketing,always taking into consideration the advanced models that today provides thiscommunication form. The research on hand will reflect the new advanced promotionmodels which are practiced by some SMEs in Kosova, these case studies will argue thecompany’s sustainability achieved by the promotion. The budgeting as an integral part ofpromotion realization, in this research will prove the possibility to save from the budgetby avoiding the classical – traditional forms of advertisement. This aspect also will beargued by case studies of SMEs in Kosova. The mass media, in this case, thecommunication with the public, in way to transmit the promotion message, request aprofound analyze when it comes to select the mediums, rating and audiencemeasurement, etc. The research will contribute not only to SMEs but also to consumersand public in general. The research will have its conclusions and recommendations whichwill enforce each of elements that require a different treatment from the one that isapplied in reality.